Note to contributors - Crossings (Crossings)
CROSSINGS: A Journal of English Studies Department of English and Humanities University of Liberal Arts Bangladesh (ULAB) crossings@ulab.edu.bd Volume 14 | December 2023 | ISSN 2071–1107 | E-ISSN 2958-3179